Psychometric evaluation of the healing after gender-based violence scale: an instrument for cross-sectional and longitudinal assessment of recovery progress for women-identifying survivors - Sinko, Laura (Journal of family violence, 2022)
Purpose: The Healing after Gender-based Violence Scale (GBV-Heal) was developed to measure the holistic recovery processes of woman-identifying survivors of gender-based violence (GBV). The GBV-Heal asks survivors to evaluate a series of statements based on perceptions of one’s lowest point and how they currently feel. These scale response options create lowest point, current feelings, and difference scores to evaluate the healing outcome cross-sectionally. This manuscript aims to evaluate the psychometric properties of the GBV-Heal to understand its usefulness for research and practice. Method: Instrument evaluation consisted of two phases analyzing online survey data from two GBV survivor samples recruited from online health research portals in the United States. In Phase One (N = 236), we conducted factor analyses and evaluated convergent/discriminant validity using depression, anxiety, posttraumatic stress, posttraumatic growth, and wellbeing measures. In Phase Two (N = 47), we evaluated GBV-Heal response consistency via test–retest within two weeks. Results: Results showed that the scale’s final model included 4 components with 18 items, explaining 61.2% and 65% of the overall scale variances for “at my lowest point” and “my current feelings,” respectively. The GBV-Heal difference score showed a weak positive correlation with wellbeing and posttraumatic growth scores and a weak negative correlation with depression, anxiety, and PTSD scores. Test–retest revealed Pearson r correlations of 0.82, 0.82, and 0.69 for the lowest point, current feelings, and difference scores respectively. Conclusion: These findings substantiate the reliability and validity of our instrument as an outcome measure that can be used both cross-sectionally and longitudinally with survivors of GBV.